A Biomimetic Platelet-Rich Plasma-Based Interpenetrating Network Printable Hydrogel for Bone Regeneration - Tang, Shijia; Wang, Lin; Zhang, Yunyang; Zhang, Feimin (Frontiers in Bioengineering and Biotechnology, 2022)
Repair of bone defects caused by trauma or diseases is the primary focus of prosthodontics. Hydrogels are among the most promising candidates for bone tissue regeneration due to their unique features such as excellent biocompatibility, similarities to biological tissues, and plasticity. Herein, we developed a type of novel biomimetic interpenetrating polymeric network (IPN) hydrogel by combining methacrylated alginate and 4-arm poly (ethylene glycol)-acrylate (4A-PEGAcr) through photo-crosslinking. Platelet-rich plasma (PRP), a patient-specific source of autologous growth factors, was incorporated into the hydrogel, and thereafter the hydrogels were biological mineralized by simulated body fluid (SBF). Physical properties of hydrogels were comprehensively characterized. In vitro studies demonstrated that the incorporation of PRP and biomineralization promoted the biocompatibility of hydrogel. Strikingly, the osteogenic bioactivities, including ALP activity, mineralized nodule formation, and expression of osteogenic markers were found substantially enhanced by this biomineralized PRP-hydrogel. Finally, a rabbit model of bone defect was employed to assess in vivo bone regeneration, micro-CT analysis showed that the biomineralized PRP-hydrogels could significantly accelerate bone generation. We believed that this novel biomineralized PRP-incorporated IPN hydrogel could be promising scaffolds for bone tissue regeneration.